KELAINAN RANGKA FETUS MENCIT (Mus musculus) GALUR BALB/C AKIBAT PEMBERIAN DEET (Diethyltoluamide) - Kusmawati, Wiwik (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2016)
The study was aimed to identify the effect of DEET on fetal skeletal abnormalities of Balb/C strain mice. Thirty five female Balb/C strain mice were used in this study. The female mice were mated with male mice used one mating method. Mice in treatment group were administered dermally with 281,25; 562,5 1125 and 2250 mg/kg BW DEET disolved in ethanol at gestation day of 6 to 15, while mice in control were administered with ethanol. Mice in group were repeated seven times. At gestation day 18, the mice were sacrificed and fetal skeletal abnormalities were observed. Bone staining subsequently was done by using Alizarin Red S. Results were analyzed by using SPSS program version 16 personal computer, one way ANOVA and multiple comparison test with significance level of 0,05. Skeletal abnormalities such as supraoccipital, sternal, vertebral, sacrocaudal and phalanx were not found in all doses administered. From these experiment we suggested that DEET has no effects in fetal skeletal abnormalities such as supraoccipital, sternal, vertebral, sacrocaudal and phalanx